Low-intensity online mindfulness-based intervention for university students with anxiety during the COVID-19 pandemic—A randomized controlled trial with 3-month follow-up - Daniel Kim-wan Young; Per Carlbring; Petrus Yat-nam Ng; Daphne Yi Ting Cheng; Joseph Qi-rong Chen; Siu-man Ng (Internet Interventions, 2023)
Objective: This study investigated the effectiveness of a low-intensity online mindfulness-based Intervention (iMBI) for alleviating anxiety in university students during the COVID-19 pandemic. Methods: In a randomized controlled trial involving 134 participants from a local university in Hong Kong, subjects were randomly assigned to either the intervention group (n = 67) or the inactive control group (n = 67). The intervention group participated in a low-intensity iMBI comprising 16 online modules and two half-day online mindfulness workshops over an eight-week period. Outcomes were measured via an online platform using standardized assessment scales, including the Beck Anxiety Inventory and the Chinese Five Facets Mindfulness Questionnaire, at three different time points: pre-intervention, post-intervention and at a three-month follow-up. Results: Intent-to-treat analysis using 2 (group) × 3 (time) repeated measures of covariance (ANCOVA) showed that the intervention group, compared to the control group, showed a significant reduction in anxiety symptoms with a medium effect size (Cohen's d = 0.5) and a significant improvement in mindfulness skills with a medium effect size (Cohen's d = 0.5) at post-intervention. The effects of the intervention in reducing anxiety and improving mindfulness persisted at the three-month follow-up. Conclusion: The results of this study demonstrate the effectiveness of the low-intensity iMBI in alleviating anxiety among university students.